The Influence of Inorganic Fillers on the Protective Properties of Epoxy Polymer Composite Materials - Danchenko, Yuliya; Andronov, Vladimir; Obizhenko, Tatyana; Kosse, Anatoliy; Khmyrov, Igor (International Journal of Engineering and Technology, 2018)
The influence of regularities of the chemical-mineralogical nature, the dispersity, and the surface properties of inorganic fillers on the protective properties of epoxy polymer composite materials have been investigated. Polymeric compositions based on epoxy resin of ED-20 brand and aliphatic amine curing agent of diethylenetriamine of DETA brand have been chosen as the research materials. The fillers were the air-dry dispersed materials of different nature: oxide, clay and quartz. The resistance of the composites to water and aqueous solutions (absorbency) was investigated by dipping the samples into an aggressive aqueous medium. For the received samples of the filled composites, thermogravimetric (TG) and differential scanning calorimetry (DSC) method were used using the SDT Q600 device manufactured by TA Instruments (USA). It has been found that the thermal stability and the absorbing capacity of the filled composites in water and aqueous acidic and alkaline mediums correlate with each other. It has been shown that to obtain materials with improved protective characteristics, it is necessary to use oxide or clay fillers with the basic (alkaline) surface function.Â Â